Práticas de abordagens operacionais no contexto das relações etnicorraciais : desafios para a formação do policial militar - Queiróz, Jamil Amorim de (2015)
The present research, at Masters level, aims to analyse the operational approaches of the military police in the context of ethnic racial relations, emphasizing the verbal, social and physical relationships during operations, whether preventive or repressive point of view. Also want to be aware of the military police training policies and its historicity; understand how police officers perceive their actions and reactions in approaches when addressing the black or white citizen; and learn how the black and white citizens perceive the approaches of the military police when directed at themselves. The research is part of the qualitative approach and inspired by the ethnographic method. The survey was conducted taking as data collection, tools documentary analysis of the Curriculum Matrix training PMMT soldiers; participant observation from operating activities, semi structured interviews with operational officers and addressed. Regarding the analysis, it was inspired by the content analysis. Ten interviews were conducted with the police, and questionnaires with twenty military police of two units, one from Cuiaba-MT and another from Várzea Grande-MT. From the content analysis, it was possible to characterize evidence of prejudice and discriminatory practices. In the ostensible police, the subject to be addressed is described as dark skinned man with tattoos, usually popular class. This highlights the need for better training of these professionals through curriculum increments; increased workload and disciplines in the humanities; debates with the movements that represent minorities, introduction of studies on ethnic racial issues, most space-time to reflect on the diversity of others, whether in initial or continuing education.